2021
DOI: 10.20508/ijrer.v11i3.12237.g8268
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Operating Parameters on Pyramid Solar Still with Phase Change Material (PCM)

Abstract: In the recent scenario, distillation with solar still plays a vital role in obtaining potable water from brackish and sea water. The inspiration for this paper is the partial availability of clean water resources and the plenty of availability water due to potential renovation into filtered water using solar energy. In this paper, an attempt is made to study the productivity of pyramid solar still. To achieve this goal, a distillation system was fabricated which incorporates a square pyramid fiber glass placed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Comparison of Efficiency at 10cm and 5cm water depth [54] The results showed that the presence of sand within the basin of the still increased its water productivity and thermal efficiency by 21.16% as shown in Figure 7. Rasheed [62], aimed to improve the performance of SS and calculate the productivity of the solar still in Babylon-Iraqi weathers by using the principle of the thermal and low-pressure vessels leading to a change in latent heat and sensible heat.…”
Section: Solar Still With Pcms As a Thermal Energy Storage Materials ...mentioning
confidence: 93%
See 1 more Smart Citation
“…Comparison of Efficiency at 10cm and 5cm water depth [54] The results showed that the presence of sand within the basin of the still increased its water productivity and thermal efficiency by 21.16% as shown in Figure 7. Rasheed [62], aimed to improve the performance of SS and calculate the productivity of the solar still in Babylon-Iraqi weathers by using the principle of the thermal and low-pressure vessels leading to a change in latent heat and sensible heat.…”
Section: Solar Still With Pcms As a Thermal Energy Storage Materials ...mentioning
confidence: 93%
“…The productivity and effectiveness of the manufactured device were increased by using PCM tubes by 40.51% and 38.25%, respectively, and decreased the cost of producing fresh water by 21.8%. Srinivas and Avssks [54] analyzed the performance of SS using pyramids solar still. The system is operated at different water depths, 5 cm, and 10 cm, along with paraffin wax material and preheated water.…”
Section: Solar Still With Pcms As a Thermal Energy Storage Materials ...mentioning
confidence: 99%